1. Math
  2. Advanced Math
  3. i need some help in solving a propositional logic proof...

Question: i need some help in solving a propositional logic proof...

Question details

I need some help in solving a propositional logic proof. The premise is A → (B ∨ C) and the conclusion is (A → B) ∨ (A → C). You are only allowed to use the rules in the image below to prove this (you are allowed sub proofs). Please show which rules were used at each step. Thanks!

Prove A → (B ∨ C) ∴ (A → B) ∨ (A → C).

Basic rules Am, n vím vím 6 9启 VE m, i-j, k-l

Solution by an expert tutor
Blurred Solution
This question has been solved
Subscribe to see this solution